The effect of acute sleep deprivation on cortisol level: a systematic review and meta-analysis - Yifei Chen; Wenhui Xu; Yiru Chen; Jiayu Gong; Yanyan Wu; Shutong Chen; Yuan He; Haitao Yu; Lin Xie (Endocrine Journal)
Acute sleep deprivation has aroused widespread concern and the relationship between acute sleep deprivation and cortisol levels is inconsistent. This study aimed to explore additional evidence and details. The PubMed, Web of Science, EMBASE, CLINAHL and Cochrane databases were searched for eligible studies published up to June 7, 2023. All analyses were performed using Review Manager 5.4 and Stata/SE 14.0. A total of 24 studies contributed to this meta-analysis. There was no significant difference in cortisol levels between participants with acute sleep deprivation and normal sleep in 21 crossover-designed studies (SMD = 0.18; 95% CI: –0.11, 0.45; p = 0.208) or 3 RCTs (SMD = 0.26; 95% CI: –0.22, 0.73; p = 0.286). Subgroup analysis revealed that the pooled effects were significant for studies using serum as the sample (SMD = 0.46; 95%CI: 0.11, 0.81; p = 0.011). Studies reporting cortisol levels in the morning, in the afternoon and in the evening did not show significant difference (p > 0.05). The pooled effects were statistically significant for studies with multiple measurements (SMD = 0.28; 95%CI: 0.03, 0.53; p = 0.027) but not for studies with single cortisol assessments (p = 0.777). When the serum was used as the test sample, the cortisol levels of individuals after acute sleep deprivation were higher than those with normal sleep.